2021
DOI: 10.1093/cid/ciab394
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 RNAemia Predicts Clinical Deterioration and Extrapulmonary Complications from COVID-19

Abstract: Background The determinants of COVID-19 disease severity and extrapulmonary complications (EPCs) are poorly understood. We characterized relationships between SARS-CoV-2 RNAemia and disease severity, clinical deterioration, and specific EPCs. Methods We used quantitative (qPCR) and digital (dPCR) PCR to quantify SARS-CoV-2 RNA from plasma in 191 patients presenting to the Emergency Department (ED) with COVID-19. We recorded p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 38 publications
0
46
0
Order By: Relevance
“…An overall of 3651 samples, from 2825 patients and 145 controls, were extracted from the 39 included studies. The studies were conducted worldwide; 16 in Asia [ 12 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], 14 in Europe [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], and 9 in North America [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. A minority of studies (8) included control samples [ 21 , 28 , 29 , 33 , 38 , 47 , 54 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An overall of 3651 samples, from 2825 patients and 145 controls, were extracted from the 39 included studies. The studies were conducted worldwide; 16 in Asia [ 12 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], 14 in Europe [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], and 9 in North America [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. A minority of studies (8) included control samples [ 21 , 28 , 29 , 33 , 38 , 47 , 54 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four of them showed that ddPCR can accurately quantify SARS-CoV-2 RNA levels, especially in immunocompromised patients and hospitalized patients with severe COVID-19 infections [ 23 , 37 , 46 , 49 ]. Furthermore, a study conducted by Ram-Mohan et al showed that ddPCR, compared to traditional RT-qPCR, was superior for detecting and quantifying SARS-CoV-2 RNAemia in hospitalized patients over a course of 30 days [ 52 ]. ddPCR was still able to detect RNAemia in 6.8% of patients at seven days, whereas RT-qPCR could not detect any RNAemia after three days [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The determinants of coronavirus disease 2019 (COVID-19) severity and extrapulmonary complications have now been well studied, and RNAemia (viral RNA in blood) has emerged as an important factor [ 1 , 2 ]. Much less is known about the determinants of postacute sequelae of COVID-19 (PASC), the persistence or development of new symptoms after the acute phase of infection, recently reported to affect as many as 87.4% of COVID-19 patients [ 3 , 4 ], primarily those with with moderate or worse severity [ 5 , 6 ].…”
mentioning
confidence: 99%